Analysis of Mathematical Representation Skills in Fraction for Madrasah Ibtidaiyah (MI) Students by Interactive Media - Nibras Alhama Najwa; Abid Ainur Rofi; Nur Hanafik; Lailatul Maghfiroh; Retno Widya Ningsih; Desi Permatasari; Annisa Nurul 'Ain; Aldila Devi Hidayati (Journal of Practice Learning and Educational Development, 2024)
This study aimed to describe an overview of the representational ability of fractional material using interactive media in the form of the "Fraction Representation" application. In this study, the approach used is qualitative. The data collection process is by providing test questions on fractional material that include indicators of mathematical representation ability. The study was conducted at Madrasah Ibtidaiyah (MI) in Madiun City, with fourth-grade students as respondents. The research subject was one of the well-known elementary schools in Madiun City, and grade IV students at the school were assigned as responders since the fraction material was studied within the class. And the school used as the research subject is one of the well-known schools in Madiun City. The results of this study are the average representation ability of students who meet the three indicators, namely visual representation, verbal representation, and symbolic representation in the medium category.